Analysis of Solid-Electrolyte Interphase at the Interface between a Graphite Negative Electrode and a Diluted Solvate Ionic Liquid-Based Quasi-Solid-State Electrolyte. Issue 14 (5th November 2020) - Kawaji, Jun; Unemoto, Atsushi; Hirano, Tatsumi; Takamatsu, Daiko; Seki, Eiji; Morishima, Makoto; Okumura, Takefumi
Abstract : The formation and growth mechanism of a solid-electrolyte interphase (SEI) on a graphite-based negative electrode was investigated to enhance the cycle life of lithium ion batteries with a quasi-solid state electrolyte (QSE). In a QSE, liquid constituents including solvate ionic liquid (SIL), diluting solvent, and additives are quasi-solidified on surface of silica particles, which ensures the safety of a 100 Wh class laminated cell. For the SIL, an equimolar complex composed of tetraethylene glycol dimethyl ether (G4) and lithium bis(trifluoromethanesulfonyl)amide (LiTFSA), was utilized. Propylene carbonate (PC) was used as diluting solvent to enhance the ionic conductivity of the SIL. Vinylene carbonate (VC) additive was introduced to form a robust SEI for inhibiting the reductive decomposition of G4 and PC. Nuclear magnetic resonance and hard X-ray photoelectron spectroscopy revealed that the decompositions of LiTFSA, PC, and G4 contributed to the SEI formation at the initial charge. During charge-discharge cycles, continuous decompositions of G4 and PC were a major reason for the SEI growth. To suppress the decomposition, charging at a low rate was introduced at beginning of the initial charge to enhance the VC decomposition and the robust SEI formation. Consequently, the decomposition of the QSE was inhibited, which enhanced its cycle life.